Low-Level Light Therapy in Orthodontic Treatment: A Systematic Review - Francesco Inchingolo; Angelo Michele Inchingolo; Giulia Latini; Gaetano Del Vecchio; Irma Trilli; Laura Ferrante; Gianna Dipalma; Andrea Palermo; Alessio Danilo Inchingolo (Applied Sciences, 2023)
This current review aims to provide an overview of the most recent research from the last 10 years on the potential of low-level light therapy (LLLT) in the orthodontic field, particularly focusing on studies about tooth movement, root resorption, pain perception during treatment, and the stability of orthodontic miniscrews. “Low-level laser,” “orthodontic,” and “LLLT” were the search terms utilized on the databases Scopus, Web of Science, and PubMed, and the Boolean operator “AND” was utilized. Of the 974 studies found, 41 publications related to our topic were included in this review. Many authors agree that LLLT could trigger an enhanced biological reaction next to the tooth in the periodontium, promoting osteoblast proliferation and differentiation, while it could also have a positive impact on bone regeneration and on increasing the rate of tooth movement, enhancing the stability of miniscrews and minimizing the occurrence of root resorption. Regarding pain management during treatment studies, the results have been controversial. Conclusions: even though further studies are still needed, the use of LLLT can improve both clinical results and patient comfort during treatment by reducing treatment duration, improving clinical aspects, such as miniscrew stability, and minimizing root resorption. Further investigations are needed to assess whether LLLT offers any real benefits regarding pain relief.